Dataset of verbal evaluation of umami taste in Europe - Iannilli E; Knaapila A; Cecchini MP; Hummel T (ELSEVIER, 2022)
The data presented here includes verbal descriptors used by Finnish, German and Italian subjects to express the quality of an umami taste solution offered in a blind fashion. The dataset refers to the research article "A cross-cultural survey of Umami Familiarity in European Countries" [1]. Data shows that a total of 106 different classes of words, including synonyms, were used by the Finnish group, 64 different classes of words, including synonyms, were used by the German group, and a total of 70 different classes of words, including synonyms, were used by the Italian group. The descriptors are reported in Excel tables and visualized in a bar graph where the length of the bars indicates the number of given answers for each class. (C) 2020 The Authors. Published by Elsevier Inc.